Associations of Comorbid Conditions and Transitions Across States of Knee Osteoarthritis in a Community‐Based Cohort. Issue 8 (1st July 2021) - Golightly, Yvonne M.; Alvarez, Carolina; Arbeeva, Liubov S.; Cleveland, Rebecca J.; Schwartz, Todd A.; Renner, Jordan B.; Murphy, Louise B.; Callahan, Leigh F.; Jordan, Joanne M.; Nelson, Amanda E.
Abstract : Objective: To examine relationships between knee osteoarthritis (KOA) and obesity, diabetes mellitus (DM), and cardiovascular disease (CVD). Methods: Associations of time‐dependent obesity, DM, and CVD with KOA transition states over approximately 18 years were examined among 4093 participants from a community‐based cohort. Transition states were 1 ) no knee symptoms and no radiographic KOA (rKOA; Kellgren‐Lawrence grade ≥2 in at least one knee), 2 ) asymptomatic rKOA, 3 ) knee symptoms only, 4 ) symptomatic rKOA (sxKOA; rKOA and symptoms in same knee). Markov multistate models estimated adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs) for associations between comorbid conditions and transitions across states, adjusting for baseline age, sex, race, education, enrollment cohort, birth year, and time‐dependent knee injury history. Results: At baseline, 40% of participants had obesity, 13% had DM, and 22% had CVD (mean age = 61 years; 34% Black; 37% male). Compared with those without obesity, those with obesity had a higher hazard of worsening from no rKOA/no symptoms to asymptomatic rKOA (aHR = 1.7; 95% CI = 1.3‐2.2) and from knee symptoms to sxKOA (aHR = 1.7; 95% CI = 1.3‐2.3), as well as a lower hazard of symptom resolution from sxKOA to asymptomatic rKOA (aHR = 0.5 [95% = CI 0.4‐0.7]). Compared with those without CVD, those with CVD had a higher hazard of worsening from no rKOA/symptoms to knee symptoms (aHR = 1.5; 95% CI = 1.1‐2.1). DM was not associated with transitions of rKOA. Conclusion: Prevention of obesity and CVD may limit the development or worsening of rKOA and symptoms.